The Effectiveness of Silica Nanocomposites in the Treatment of Breast and Liver Cancer Through a Natural Physical Field - Yehia, Hesham Mohamed Abdal-Salam; Said, Said Mahmoud (British Journal of Healthcare and Medical Research, 2022)
Cancer survival rates, or survival statistics, show you the percentage of people who survive a specific type of cancer for a specific period of time. Cancer statistics use a five-year survival rate. Survival rates are usually given as percentages. For example, the five-year survival rate for breast or liver cancer is 77 percent. This means that, of all people diagnosed with breast or liver cancer, 77 out of 100 live to five years after being diagnosed with cancer. In contrast, 23 out of every 100 people die within five years of being diagnosed with breast or liver cancer. Despite the development of diagnostic and treatment methods, there is a significant meaning with chemotherapy, and a low cure rate. The current research aims to reveal the effectiveness of the impact of heat-treated silica nanoparticles with the addition of titanium dioxide on breast and liver cancer cells. The tests were carried out at the National Cancer Institute in the Arab Republic of Egypt, and the results showed a significant improvement in the rate of infection, as the percentage of tumors decreased by about 71%, which contributes significantly to the development of the patient's treatment condition.